The influence of urban park green spaces, plant materials organization and spatial design and pattern towards carbon sequestration rate - Othman, Rashidi; Suid, Suhaili; Hashim, Khairusy Syakirin Has-Yun; Hj. Baharuddin, Zainul Mukrim (2018)
Urban parks have been viewed as an important part of urban and community development that will facilitate social cohesion by creating space for social interactions and provide natural habitats. Apart from that, the value of urban parks nowadays as part of the living environment as reflected in higher real estate prices especially in housing township development. Urban parks also function as a carbon sink by reducing air pollutant levels and sequestering atmospheric carbon dioxide (CO2). This study provides a case study of the quantification of carbon sequestration rate by a selected urban park with hybrid design landscape setting in Putra Heights, Mukim Damansara, Selangor, a rapidly urbanized and populated city surrounded by highly developed residential areas and located nearby Light Rail Transit (LRT) and ELITE highway. The carbon sequestration rate was calculated by biomass equations, using field data inventory, measurement, plan analysis and survey data analysis. This study aimed to calculate, predict and compare carbon sequestration rate produced by plant materials through hybrid design landscape setting at a certain period of time. The significance outcome of this study is the determination of key factors that influenced the Carbon Sequestration Rate at different design landscape setting. This study proved that higher plants specification plays an important role in sequestering more carbon. The larger green area also contributes to higher carbon sequestration rate. These findings will become a novel landscape design approach to neutralize carbon emission with cost-effective and environmentally friendly.